Dewan Redaksi Rekayasa Jurnal Teknik Sipil Volume 7 Nomer 1 Juni 2022 - Dewan Redaksi Rekayasa Jurnal Teknik Sipil Volume 7 Nomer 1 Juni 2022 (Rekayasa: Jurnal Teknik Sipil, 2022)
Rekayasa Jurnal Teknik Sipil Volume 7 Nomer 1 Juni 2022